Scaling up climate information services through public-private partnership business models - Partey, Samuel T.; Nikoi, Gordon K.; Ouédraogo, Mathieu; Zougmoré, Robert B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Between 2011 and 2017, CCAFS West Africa piloted how the dissemination of climate information services (CIS) to farmers in its climate-smart village sites (Lawra and Jirapa) in Ghana could help them avert risks associated with climate change and variability. The pilot was executed with 1000 profiled and geo-referenced farmers (33% women) through a collaboration with a private information and communication technology (ICT) company, Esoko in Ghana and the Ghana Meteorological Agency (GMet). During the pilot, Esoko delivered processed weather information received from GMet and other sources to farmers using mobile phone platforms. The Esoko platform also allows farmers to access a call center where CIS is delivered to them vocally in their local dialect. The forecast information included the total rainfall, the onset and end of the rainy season, and a 10-day forecast during the rainy season (Partey et al., 2018). In addition to the weather forecast information, farmers receive market alerts and agro-advisories that are intended to help them understand and apply the received information.